Respostas
respondido por:
3
f(x) = x + 2
g(x) = x² - 2
f(x) = x + 2
f[g(x)] = colocar o g(x) dentro de "x"
x + 2 = (x² - 2)+ 2 no lugar de "x"
g(x) = x² - 2
f(x) = x + 2
g[f(x)] = "f" dentro do "g"
= (x+ 2)² - 2
Assim:
f[g(x)] = g[f(x)]
x² - 2 + 2 = (x + 2)² - 2
x² - 2 + 2 = x² + 2.2.x + 4 - 2
x² = x² + 4x + 2
x² - x² = 4x + 2
0 = 4x + 2
- 2 = 4x
4x = - 2
x = -2/4
x = - 1/2
R.: x = - 1/2
g(x) = x² - 2
f(x) = x + 2
f[g(x)] = colocar o g(x) dentro de "x"
x + 2 = (x² - 2)+ 2 no lugar de "x"
g(x) = x² - 2
f(x) = x + 2
g[f(x)] = "f" dentro do "g"
= (x+ 2)² - 2
Assim:
f[g(x)] = g[f(x)]
x² - 2 + 2 = (x + 2)² - 2
x² - 2 + 2 = x² + 2.2.x + 4 - 2
x² = x² + 4x + 2
x² - x² = 4x + 2
0 = 4x + 2
- 2 = 4x
4x = - 2
x = -2/4
x = - 1/2
R.: x = - 1/2
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás